Female and juvenile burrow-digging in Allocosa brasiliensis, a South American sand-dwelling wolf spider - de Simone, Gabriel Alejandro (2015)
Allocosa brasiliensis is a sand-dwelling wolf spider that constructs burrows along the coasts of rivers, lakes and the Atlantic Ocean in Argentina, Brazil and Uruguay. This species shows a reversal in typical sex roles in spiders: females wander searching for males and initiate courtship, while both females and males are selective when taking mating decisions. Females prefer to mate with males that show long burrows. As burrow digging in the sand seems to be an energetically expensive activity, we would expect differences in burrow characteristics according to developmental stage and selection pressures. Our aim was to describe female and juvenile digging behavior in A. brasiliensis and report burrow dimensions, comparing the results with data available for males of this species. We placed each individual (n = 30 of each category) in glass cages with sand as substrate and recorded burrow construction under laboratory conditions. Only five females and nine juveniles constructed burrows after 72 hours. Burrow dimensions did not show significant differences between females or juveniles, but burrow length was markedly lower that reports for males of this species. Burrow digging was stereotyped both in females and juveniles, following a sequence of behavioral units repeated in a cycle. Digging behavior would be highly conserved in A. brasiliensis. However, variations in burrow digging behavior and final burrow dimensions would reflect differences in strategies according to sex and stage.